Pengendalian Kualitas Pengelasan Pada Proyek Pipeline Sabar#2 - Teguh Junianto; Imam Bayhaqi; Erna Rahayu (LPPM Politeknik Jambi, 2020)
PT. ICG is a company that handles the pipeline welding process at PetroChina Jabung Ltd. The welding process carried out is cutting, rolling, pressing and painting. The problem that occurs is that 243 defects are found from the output of 457 welding points. The types of defects after the welding process included 106 points of Root Cancellation defects, 99 points of Incomplete fusion, 29 points of Porosity, 8 points of Slug Inclusion, and 1 point of Tungsten Inclusion. This study aims to control quality by looking at the sigma value of the pipeline production process and analyzing the improvements that should be made to reduce the defects that occur. The results of the calculation of Defect Per Million Opportunities (DPMO) show that the number of welding defects that arise every one million opportunities is 174,10. The quality of the welding process in the pipeline Sabar # 2 project is at a sigma value of 2,43 with a DPMO value of 174,10. From the results of the sigma value obtained, this value is still far from the expectations of Petrochina's management to achieve a minimum sigma value of 4,0. The potential causes of weld defects include welding machines, work errors, work methods and work environment.